UPACARA TRADISI MASA KEHAMILAN dalam Masyarakat Jawa - Suliyati, Titiek (Sabda: Jurnal Kajian Kebudayaan, 2012)
Javanese society possesses traditional ceremonies to their life cycle and natural phenomenon. These traditional ceremonies conducted from generation to generation carry symbols of good expectations and moral education as local wisdom rooted from the past sociocultural thoughts and senses.This article discusses traditional ceremonies among the Javanese society, focusing on the pregnancy period of Mapati, Tingkepan, Mrocoti, Ndadung and Ndaweti.